Femto-second and nanoscale hot carrier dynamics in ZnO/Al2O3/Ag-NWs/FTO heterojunction - Singh, Ranveer; Shin, Heecheol; Nah, Sanghee; Park, Ji Yong; Seo, Hyungtak (Journal of Alloys and Compounds, 2021)
Carrier injection in wide-band-gap materials is attracting a considerable research interest due to its potential applications in hot carrier solar cells, photocatalysis, next generation of ultrafast nanophotonics, etc. Herein, we fabricate a ZnO/Al2O3/silver-nanowires heterostructure using sputtering and atomic layer deposition techniques and report the tunneling dynamics of hot carriers via Al2O3 layer, revealed by nanoscale current maps and bulk current-voltage measurements. Atomic force microscopic and scanning electron microscopic studies reveal the uniform distribution of granular nanostructures (of ZnO thin films) and random distribution of Ag-NWs. The absorption measurements of the heterostructure show light absorption in wide wavelength range. In addition, the thickness of tunneling layer (Al2O3 films) was varied and 2 nm-thick Al2O3 layer provides the relatively easy charge transport due to resonant tunneling effect, as is confirmed using electrostatic force microscopy, Kelvin probe force microscopy, and conductive atomic force microscopy measurements. Further, current-voltage characteristics reveal the photocurrent under different wavelength illumination for 2 nm-thick Al2O3 layer heterostructure. Interestingly, the ZnO/Al2O3 (2 nm)/Ag-NWs device demonstrates fast decay and hot carriers transfer from Ag-NWs to ZnO, as is evident from the femtosecond pump-probe transient absorption measurements. Our finding paves an effective approach for improving the hot carrier injection efficiency in the wide band gap materials for use in photovoltaics and photocatalysis applications.
Keywords: Ag$++$; Carrier dynamics; Electrostatic force microscopy; Femtoseconds; Hot-carriers; Nano scale; Silver nanowires; Tunneling; Wide band-gap material; ZnO:Al; Electrostatic force microscopy; Hot carrier; Silver nanowires; Tunneling